Seorang Pasien Laki-Laki 70 Tahun dengan Hemichorea di Rumah Sakit Daerah Cut Meutia Aceh Utara - Siti Farisa; Intan Sahara Zein (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Hemichorea is a hyperkinetic movement disorder characterized by involuntary, rapid, irregular movements affecting one side of the body. It is a rare neurological condition commonly associated with lesions of the basal ganglia, particularly the subthalamic nucleus. The etiology of hemichorea is diverse, including ischemic or hemorrhagic stroke, metabolic disturbances such as non-ketotic hyperglycemia, infections, neoplasms, and autoimmune disorders. In some cases, hemichorea may represent the initial manifestation of acute ischemic stroke, which can lead to delayed diagnosis and management due to its uncommon presentation. Diagnosis is established through careful clinical evaluation, neurological examination, laboratory investigations, and neuroimaging modalities such as computed tomography or magnetic resonance imaging. Management is mainly symptomatic and etiological, focusing on controlling the underlying cause, especially optimal glycemic control, and administering medications that reduce dopaminergic activity. The prognosis of hemichorea is generally favorable, particularly when the underlying condition is promptly identified and appropriately treated. This case highlights the importance of recognizing hemichorea as a potential manifestation of stroke and metabolic disorders to ensure timely diagnosis and effective management.